IMPLEMENTASI JARINGAN SYARAF TIRUAN UNTUK PREDIKSI CUACA PADA PLTA SUMATERA BARAT - Boby Putra Lubis; Deddy Prayama; Hidra Amnur (SOTVI - Society of Visual Informatics, 2022)
The atmosphere that often changes erratically at this time causes weather forecasts to be unpredictable [1]. By using the Neural Network (NN) method for weather prediction, it is possible to estimate weather conditions more accurately [2]. With the help of the backpropagation algorithm which is commonly used for training data purposes, which can compare each sample data. In every process that occurs so as to get a minimum value on the Mean Square Error (MSE) [1]. The development of this program will be based on a website so that all who need information about weather forecasts for the next few months can view or search easily.